Jewish Leadership in Roman Palestine from 70 C.E. to 135 C.E.. - Choi, Junghwa. (Ancient Judaism and Early Christianity, 2013)
Reconstructing Jewish socio-political leadership of the late Second Temple and Talmudic periods, this book suggests that the period between two great revolts is the best period to study leadership dynamics. Prior to the emergence of the rabbinic leadership, biblically modelled leadership was still a realistic option, often co-existing with non-biblical polity. It also attempts to reconstruct the Jewish socio-political leadership of this period by examining how consistently the ideas of leadership that were available before 70 C.E. were followed after 70 C.E.